Pemanfaatan cybercounseling pada layanan bimbingan dan konseling di sekolah - Maharani Putri (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
in an increasingly developing era, the world is now entering the era of society 5.0 where humans coexist with existing technology. In every day the majority of the world community has carried out activities with the help of the internet. The development of technology in almost all fields has progressed including the provision of guidance and counseling services in schools. Nowadays, guidance and counseling services have progressed by following the times by implementing online counseling services or cybercounseling. With cybercounseling services, service delivery has no limitations in distance and time. This research was conducted to find out how the utilization of cybercounseling in schools. This research uses a literature study method in the form of journal articles. The results of the research obtained from cybercounseling services have benefits for guidance and counseling teachers with their students. Guidance and counseling teachers are expected to continue to make new innovations to be able to conduct counseling in an easy and effective way for their students.